2D PdAg Alloy Nanodendrites for Enhanced Ethanol Electroxidation. Issue 11 (16th January 2018) - Huang, Wenjing; Kang, Xiaolin; Xu, Cheng; Zhou, Junhua; Deng, Jun; Li, Yanguang; Cheng, Si
Abstract: The development of highly active and stable electrocatalysts for ethanol electroxidation is of decisive importance to the successful commercialization of direct ethanol fuel cells. Despite great efforts invested over the past decade, their progress has been notably slower than expected. In this work, the facile solution synthesis of 2D PdAg alloy nanodendrites as a high‐performance electrocatalyst is reported for ethanol electroxidation. The reaction is carried out via the coreduction of Pd and Ag precursors in aqueous solution with the presence of octadecyltrimethylammonium chloride as the structural directing agent. Final products feature small thickness (5–7 nm) and random in‐plane branching with enlarged surface areas and abundant undercoordinated sites. They exhibit enhanced electrocatalytic activity (large specific current ≈ 2600 mA mg Pd − 1 ) and excellent operation stability (as revealed from both the cycling and chronoamperometric tests) for ethanol electroxidation. Control experiments show that the improvement comes from the combined electronic and structural effects. Abstract : 2D PdAg alloy nanodendrites are prepared in solution with assistance from a cationic surfactant with a long alkyl chain. They feature small thickness and random in‐plane branching with enlarged surface areas and abundant undercoordinated sites. When evaluated as an electrocatalyst for the ethanol oxidation reaction, they demonstrate impressive electrocatalytic activity and stability superior to most other competitors.